Fibrinogen and elastin bind to the same region within the A domain of fibronectin binding protein A, an MSCRAMM of Staphylococcus aureus - FOSTER, TIMOTHY (My University, 2007)
The fibronectin binding protein, FnBPA, is a multifunctional microbial surface component recognizing adhesive matrix molecule (MSCRAMM) that promotes bacterial adherence to immobilized fibrinogen and elastin via the N-terminal A domain. The binding site for fibrinogen and elastin was localized to subdomains N2N3. A three-dimensional structural model of FnBPA was created based on the known crystal structure of the domains N2N3 of clumping factor A (ClfA). The role of individual residues in the putative ligand binding trench was examined by testing the affinity of mutants for fibrinogen and elastin. Two residues (N304 and F306) were crucial for binding both ligands and are in the equivalent positions to residues known to be important for fibrinogen binding by ClfA. A peptide comprising the C-terminus of the gamma-chain of fibrinogen and a monoclonal anti-rAFnBPA antibody were potent inhibitors of the FnBPA-elastin interaction. This suggests that FnBPA binds to fibrinogen and elastin in a similar manner. Amino acid sequence divergence of 26.5% occurred between the A domains of FnBPA from strains 8325-4 and P1. Most variant residues were predicted to be located on the surface of domains N2N3 while few occurred in the putative ligand binding trench and the latching peptide explaining limited immunocross reactivity while ligand binding activity is conserved.